Application of Recombinant VII Activated Coagulation Factor for Children with Resistant Coagulopathy Caused Sepsis - N. Bgane; A. Trembach (Медицинский вестник Юга России, 2010)
Purpose: To investigate the effectiveness of recombinant VII activated coagulation factor in complex therapy of children with resistant coagulopathy caused by sepsis. Materials and Methods: 38 children from 2 months to 17 years old were investigated with resistant coagulopathy caused by sepsis and using of recombinant VII activated coagulation factor. Patients were divided into 2 groups. The first group concluded the children before 1 year old; the second group concluded the children after 1 year old. Results: The children of first group revealed the improvement of clinical and laboratory status after two intravenous applications (2 hours between using) of recombinant VII activated coagulation factor. The single use of recombinant VII activated coagulation factor was sufficient for children of second group. There was no effect in both groups of children with sepsis and multiorgan failure. Summary: The application of recombinant VII activated coagulation factor is effective for therapy of children with resistant coagulopathy caused by severe sepsis.